2022
DOI: 10.3390/nano12040697
|View full text |Cite
|
Sign up to set email alerts
|

Extended Line Defect Graphene Modified by the Adsorption of Mn Atoms and Its Properties of Adsorbing CH4

Abstract: Extended line defect (ELD) graphene is a two-dimensional (2D) topologically defective graphene with alternate octagonal and quadrilateral carbon rings as basic defective units. This paper reports on the CH4 adsorption properties of ELD graphene according to the first principles of density functional theory (DFT). The effects on the CH4 adsorption of ELD graphene when modified by a single Mn atom or two Mn atoms were investigated, respectively. An ELD-42C graphene configuration consisting of 42 C atoms was firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Manganese ore is an important strategic mineral resource. 1 China is the world's main producer and consumer of manganese ore, with reserves of about 570 million tons, accounting for about 34% of the world's total reserves. Manganese ore is mainly used in the production of steel, alloys, batteries, and chemical products.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese ore is an important strategic mineral resource. 1 China is the world's main producer and consumer of manganese ore, with reserves of about 570 million tons, accounting for about 34% of the world's total reserves. Manganese ore is mainly used in the production of steel, alloys, batteries, and chemical products.…”
Section: Introductionmentioning
confidence: 99%
“…Two research works in this Special Issue studied the adsorption and storage of natural gases on defined nanomaterials. [ 7 , 8 ] First, Shkolin et al [ 7 ] synthesized an active carbon nanomaterial from cheap peat raw materials and investigated its structural–energetic and adsorption properties towards natural gas (ANG). The study provides insights into the solution for improving the safety and storage capacity of low-pressure gas storage systems.…”
mentioning
confidence: 99%
“…The study provides insights into the solution for improving the safety and storage capacity of low-pressure gas storage systems. Second, Zhang et al [ 8 ] reported the CH 4 adsorption properties on extended line defect (ELD) graphene according to the first principles of density functional theory (DFT). The Mn modification of ELD graphene was found to significantly affect the CH 4 adsorption.…”
mentioning
confidence: 99%